THE RELATIONSHIP AMONG LEARNING INDEPENDENCE, LEARNING DISCIPLINE AND NUMERICAL ABILITY WITH MATHEMATICS LEARNING OUTCOMES OF STUDENTS GRADE VII SMP MUHAMMADIYAH 9 YOGYAKARTA - Nadine Deninta Dido; Nur Arina Hidayati (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
The low of mathematics learning outcome is influenced by many factors. Learning independence, learning discipline and numerical ability are some of the factors that may affect the mathematics learning outcomes of students. Therefore, this research was conducted in order to determine whether there is a positive and significant relationship between learning independence, learning discipline and numerical ability with mathematics learning outcomes of students grade VII SMP Muhammadiyah 9 Yogyakarta in even semester of the academic year 2015/2016. The population in this research was all students of class VII SMP Muhammadiyah 9 Yogyakarta in the academic year 2015/2016 consisting of 5 classes with a total of 183 students. Random sampling techniques used to get class samples and collected VII C as a sample that consists of 37 students. Techniques of data collection were conducted by questionnaire to learning independence and learning discipline, being a test method for numerical ability and mathematics learning outcomes. Test instruments used validity and reliability. Prerequisite test analysis using homogeneity, normality test, independent, and linearity test. Hypothesis testing data analysis using simple linear regression analysis and multiple regression analysis and correlation. The results showed that there is a positive and significant correlation among learning independence, learning discipline and numerical ability with mathematics learning outcomes with F count = 12.1486271 > F table = 3.27 multiple correlation coefficient (R) is 0.497054456 and the coefficient determination (R2) is 0.5248098361. While multiple regression equation Â = 91.67974362 + 0.2721162468X1 + 0.4013598791X2 + 0.4720896167X3, relatively contribution (X1) = 25.78224833%, the relative contribution (X2) = 36.63257052%, the relative contribution (X3) = 37.58518115% and effective contribution (X1) = 13.53077742%, the effective contribution (X2 ) = 19.22513318% and the effective contribution (X3) = 19.72507261%.